Teacher strategy in using animated videos in learning English - Karmila Olii; Andi Nurwati (English Education Department, 2022)
This research aims to identify and describe the teacher's strategy in using animated videos in learning English. The subject of this study involved an English teacher at SMPN 1 Tabongo. This research employed descriptive qualitative research method. Participants were taken using purposive sampling technique. Data was collected from observation sheets, semi-structured interviews, and documentation. The data were then analyzed through the stages of data reduction, data presentation, and drawing conclusions. The results showed that the use of animation video as media in English learning is able to support two-way learning process between teacher and students. The teacher's strategy of using English animation videos can help students understand the material. In addition, through the use of English Animation videos, it can stimulate the creativity, interest, and motivation of the teacher, and also through the use of English Animation videos, students' knowledge, preparation of teaching materials, selection of materials, teacher’s delivery methods have shown good development.